Congenital Harlequin Ichthyosis: A Rare genetic Disorder - Parveen, Umme; Sultana, Kiswar; Alam, Mia Mamtaz Daulat (Dhaka Shishu (Children) Hospital Journal, 2020)
Abstract not available DS (Child) H J 2019; 35(2) : 179-181